Structural models for policy-making: Coping with parametric uncertainty - Philipp Eisenhauer; Janos Gabler; Lena Janys (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The ex-ante evaluation of policies using structural econometric models is based on estimated parameters as a stand-in for the truth. This practice ignores uncertainty in the counterfactual policy predictions of the model. We develop a generic approach that deals with parametric uncertainty using uncertainty sets and frames model-informed policymaking as a decision problem under uncertainty. The seminal human capital investment model by Keane and Wolpin (1997) provides us with a well-known, influential, and empirically-grounded test case. We document considerable uncertainty in their policy predictions and highlight the resulting policy recommendations from using different formal rules on decision-making under uncertainty.
Keywords: 330; Wirtschaftspolitik; Makroökonometrie; Strukturmodell; Schätztheorie; Risiko; Entscheidung unter Unsicherheit; Theorie